2018
DOI: 10.2214/ajr.17.18295
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Ultrasound Identifies Residual Nodal Disease After Chemotherapy: Results From the American College of Surgeons Oncology Group Z1071 Trial (Alliance)

Abstract: OBJECTIVE The purpose of this study is to determine lymph node features on axillary ultrasound (US) images obtained after neoadjuvant chemotherapy that are associated with residual nodal disease in patients with initial biopsy-proven node-positive breast cancer. SUBJECTS AND METHODS All patients had axillary US performed after neoadjuvant chemotherapy. Axillary US images were centrally reviewed for lymph node size, cortical thickness, and cortical morphologic findings (type I indicated no visible cortex; typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…There are also reports that sensitivity and specificity of axillary ultrasound alone after NAC are 55% and 88 %, respectively, which is very close to the results of our research (You et al, 2015;Baumgartner et al, 2018;Le-Petross et al, 2018). However, pathological confirmation of the ycN stage is very important in surgical decision making, especially taking in to account that ultrasound method is highly operator dependent.…”
Section: Discussionsupporting
confidence: 89%
“…There are also reports that sensitivity and specificity of axillary ultrasound alone after NAC are 55% and 88 %, respectively, which is very close to the results of our research (You et al, 2015;Baumgartner et al, 2018;Le-Petross et al, 2018). However, pathological confirmation of the ycN stage is very important in surgical decision making, especially taking in to account that ultrasound method is highly operator dependent.…”
Section: Discussionsupporting
confidence: 89%
“…31 It was also reported that the US could identify residual nodal disease after NAC with clearly defined standards. 20 Thus, the US has been considered the most convenient and economic noninvasive method to evaluate the axilla, though it was not superior to other methods for the assessment of primary tumor response to NAC. 32 Therefore, we added the post-NAC AUS status in the analysis of our study and demonstrated that it was the most significant predictor of non-SLN metastasis (OR: 4.933, p=0.005).…”
Section: Discussionmentioning
confidence: 99%
“…Axillary ultrasound (AUS) is a convenient and useful imaging method for clinical axilla staging prior to surgery in breast cancer patients with or without NAC. [19][20][21] Thus, numerous institutions have adopted AUS as a routine practice to evaluate axillary status prior to surgery in the management of patients with breast cancer. However, to the best of our knowledge, there has been no model including pre-surgery AUS to predict the risk of non-SLN metastasis in patients after NAC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported, however, that the high false‐negative rate associated with SNB after NACT can be reduced by targeted axillary dissection of positive lymph nodes with the use of I‐labelled seed, clip or wire localization. Recent data from the ACOSOG Z1071 (Alliance) trial indicate that axillary ultrasound examination after NACT is useful for assessment of nodal response, and can direct further axillary management. Considering current reservations relating to SNB after NACT, it is paramount that any axillary staging after NACT is undertaken using the most sensitive and accurate technique and, based on the results of the present analysis, US‐CNB is the superior diagnostic test to use.…”
Section: Discussionmentioning
confidence: 99%